Computer use, language, and literacy in safety net clinic communication. (6th June 2016) - Ratanawongsa, Neda; Barton, Jennifer L; Lyles, Courtney R; Wu, Michael; Yelin, Edward H; Martinez, Diana; Schillinger, Dean
Abstract : Objective: Patients with limited health literacy (LHL) and limited English proficiency (LEP) experience suboptimal communication and health outcomes. Electronic health record implementation in safety net clinics may affect communication with LHL and LEP patients. We investigated the associations between safety net clinician computer use and patient-provider communication for patients with LEP and LHL. Materials and Methods: We video-recorded encounters at 5 academically affiliated US public hospital clinics between English- and Spanish-speaking patients with chronic conditions and their primary and specialty care clinicians. We analyzed changes in communication behaviors (coded with the Roter Interaction Analysis System) with each additional point on a clinician computer use score, controlling for clinician type and visit length and stratified by English proficiency and health literacy status. Results: Greater clinician computer use was associated with more biomedical statements (+12.4, P  = .03) and less positive affect (−0.6, P  < .01) from LEP/LHL patients. In visits with patients with adequate English proficiency/health literacy, greater clinician computer use was associated with less positive patient affect (−0.9, P  < .01), fewer clinician psychosocial statements (−3.5, P  < .05), greater clinician verbal dominance (+0.09, P  < .01), and lower ratings on quality of care and communication. Conclusion: Higher clinician computer use was associated with more biomedical focus with LEP/LHL patients, and clinician verbal dominance and lower ratings with patients with adequate English proficiency and health literacy. Discussion: Implementation research should explore interventions to enhance relationship-centered communication for diverse patient populations in the computer era.